THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE - Lukiman, Livia; Wirianata, Henny (Graduate Program of Universitas Tarumanagara, 2024)
Companies engage in CSR and GCG activities because they believe it will improve their financial performance. Income uncertainty as an impact of pandemic makes it interesting to examine how company will operate throughout 2019-2021. This study uses data on financial dan sustainability reports from five sectors of manufacturing companies. The proportion of institutional ownership and independent commissioners, as well as the audit quality, are used to calculate GCG. The disclosed activities in SR are measured for CSR. The modified Jones model is used to measure earnings management. ROA, EPS, and Tobin's Q are used to measure financial performance. PLS method and WarpPLS v.8.0 was used to examine the hypotheses in this study. The study’s findings demonstrate that GCG significantly affect financial performance and earnings management. CSR has a substantial effect on financial performance while having no effect on earnings management. Earnings management have no significant effect on financial performance. Meanwhile, earnings management is considered unable to mediate the effect of GCG and CSR on financial performance.